PENGARUH ROA, ROE, DER, DAN KURS RUPIAH TERHADAP PERGERAKAN HARGA SAHAM PADA MASA PANDEMI COVID-19 (Pada Perusahaan Sub Sektor Otomotif yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2021) - Rizal Riyadi; Solihin Solihin; Karsam Karsam; Basyirudin Nur (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to: (1) To determine the effect of Return On Assets on stock prices in the automotive sub-sector in Indonesia which is listed on the Indonesian stock exchange, (2) To determine the effect of Return On Equity on stock prices in the listed automotive sub-sector in Indonesia. on the Indonesian stock exchange, (3) To determine the effect of the Debt to Equity Ratio on stock prices in the automotive sub-sector in Indonesia listed on the Indonesian stock exchange, (4) To determine the effect of the Rupiah exchange rate on stock prices in the listed automotive sub-sector in Indonesia. on the Indonesian stock exchange, (5) To determine the effect of Return On Assets, Return On Equity and Debt to Equity Ratio and the Rupiah Exchange Rate together on stock prices in the automotive sub-sector in Indonesia listed on the Indonesian stock exchange. The total population is 13 issuers and the number of samples is 6 issuers. The sample used is non-probability with purposive sampling technique. The data used is secondary data derived from the annual published financial report presented on the IDX website (www.idx.co.id). Data processing uses the Statistical Package for the Social Sciences (SPSS). From the results of the study obtained the following data: (1) ROA has a partial and significant effect on stock prices. (2) ROE partially has a negative and significant effect on stock prices. (3) DER partially has no effect on the stock price. (4) ROA, ROE, and DER as well as the Rupiah Exchange Rate simultaneously affect the Stock Price.